SURVEY STATUS GROSS MOTOR SKILL PADA SISWA KELAS RENDAH USIA 7 -9 TAHUN TINGKAT SEKOLAH DASAR (Studi pada Sekolah Dasar di Kecamatan Sumberpucung, Kabupaten Malang) - Andi Prisma Mukti; Lokananta Teguh Hari Wiguno (JOURNAL SAINS STUDENT RESEARCH, 2025)
Gross motor skills are important for children's growth and development, these motor skills are individual activities related to performance to achieve various skills learned from childhood to elementary school. This study aims to determine the level of motor quality of students aged 7-9 years in A-accredited public elementary schools in Sumberpucung District, Malang Regency. This research uses a quantitative type of research, this is because the data obtained will be processed in the form of numbers, and this research uses a descriptive approach model which aims to explain a phenomenon that occurs. Apart from that, in this research a survey method was used to calculate the values ​​of existing variables. In this research, a survey method was carried out in the form of examining the basic motor movements of elementary school students with an average age of 7 to 9 years. This research used a sample of 272 students using the TGMD-2 which was considered to have a high level of validity. This research obtained the average score for the low class student category with a score of 38.59926471, and a standard deviation value of 4.585924178.